Going the Distance: Will Family-to-Work Role Conflict Mediate the Relationship between COVID-19 Distance Learning and Career Expectations and Turnover Intentions? - Coltman Burnett, Karissa (My University, 2021)
In response to the worldwide COVID-19 pandemic, many organizations pivoted to teleworking and schools implemented distance learning, resulting in many parents finding themselves teleworking while also overseeing their child(ren)’s distance education. As distance learning responsibilities increase, role theory (Biddle & Thomas, 1966) explains that inter-role conflict will stem from incompatibilities between work and distance learning supervision responsibilities. The current study posits that work interference from distance learning and gender will be positively associated with lowered career expectations and higher turnover intentions, and that family-to-work conflict mediates the relationship. A convenience sample of 107 teleworking adults with children in distance learning were recruited via social media to complete a Qualtrics survey. Moderate correlations were found between gender, distance learning, and family-to-work conflict, with family-to-work conflict mediating the relationship between distance learning and lower career expectations. Women reported more involvement in distance learning, more family-to-work conflict and lower career expectations than men; however, family-to-work conflict as mediator between distance learning and turnover intentions was not supported and gender did not predict turnover intentions. An indirect effect was found of distance learning on turnover intentions, sequentially mediated by family-to-work conflict and career expectations. The study increases awareness of the impacts of the COVID-19 pandemic on working parents, particularly mothers, carrying the burden of their child’s distance learning responsibilities and highlights the opportunity for further research into interventions to help mitigate the impacts of the pandemic on the long-term career achievements of working mothers. Keywords: COVID-19, distance learning, gender, family-to-work conflict, career expectations, turnover intention
Keywords: COVID-19, distance learning, gender, family-to-work conflict, career expectations, turnover intention